(untitled) (Res Gesta, 2025)
The purpose of this paper is to investigate the First Argentine Primitive Book Exhibition organized by the Catholic Culture Courses (CCC) in November 1928. This event, dedicated to exhibit copies of the dawn of Argentine printing, represented a tactic of intervention of the Catholic laity in the public sphere and a bet of intellectual dispute. It is hypothesized that this enterprise was envisioned as a positioning strategy of the CCCs in the wider cultural field by trying to raise the voice of actors linked to Catholicism on a bibliographic corpus that had been the subject of study among various exponents of the academic field, especially historians and bibliophiles. Its approach is central not only to recover the scene of tensions but also of encounters, negotiations and crossed agents in the construction of a field of expertise on the history of the beginnings of national printing during the first decades of the twentieth century.